2021
DOI: 10.1002/aelm.202100999
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Resistive Switching in Layered InSe via Electrochemical Cation Diffusion

Abstract: 2D materials are increasingly being investigated for their nonvolatile switching properties as a step toward downscaling of core electronic elements. Here, the interplay between electrochemically active silver (Ag) cations and layered indium selenide (InSe), a 2D metal monochalcogenide, is investigated to demonstrate a nonvolatile switching device. Detailed microscopic characterization supported with density functional theory calculations reveals cationic filamentary‐based nonvolatile switching mechanism of γ‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…[ 13–15 ] With resistive switching behaviors in 2D materials constantly observed, 2D materials have opened a new avenue of pursuing novel materials with excellent switching properties and shown great potential for application in RRAM. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13–15 ] With resistive switching behaviors in 2D materials constantly observed, 2D materials have opened a new avenue of pursuing novel materials with excellent switching properties and shown great potential for application in RRAM. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] With resistive switching behaviors in 2D materials constantly observed, 2D materials have opened a new avenue of pursuing novel materials with excellent switching properties and shown great potential for application in RRAM. [16,17] 2D semiconducting bismuth oxyselenide (Bi 2 O 2 Se) has emerged with excellent properties and shown great potential in electronics and optoelectronics. Bi 2 O 2 Se based field-effect transistors with very high carrier mobility (>20 000 cm 2 V -1 s -1 ) and low subthreshold swing (≈65 mV dec -1 ) have been reported.…”
mentioning
confidence: 99%
“…The monolayer TMDs provide possibilities for fabricating ultrathin switching layers, which is beneficial for device scaling as well as for very low-power applications. Mazumder et al reported bipolar switching in a CBRAM device fabricated with a layered InSe 2D monochalcogenide switching layer ( Figure 5 a,b) [ 50 ]. As shown in Figure 5 c, the thin (8.8 nm) layered switching material-based device presented nonvolatile switching with a stable retention time of >10 5 s, maintaining an ON/OFF ratio of >10 3 .…”
Section: Electrode and Switching Materialsmentioning
confidence: 99%
“…Reprinted from Ref. [ 50 ]. ( d ) The typical I–V characteristics of a CBRAM device with structure Cu/GeTe/TiN presenting bipolar switching.…”
Section: Figurementioning
confidence: 99%
“…The integration of two-dimensional (2D) materials into electronic circuits gives promise of taking steps beyond the conventional metal-oxide-based technologies 1 4 . Being implemented in microelectronic platforms, e.g., memristors 1 , 5 – 11 , such materials with their advanced functionality and outstanding capability circumvent innovative challenges.…”
Section: Introductionmentioning
confidence: 99%